2005
DOI: 10.1073/pnas.0504662102
|View full text |Cite
|
Sign up to set email alerts
|

Role of domestic ducks in the propagation and biological evolution of highly pathogenic H5N1 influenza viruses in Asia

Abstract: Wild waterfowl, including ducks, are natural hosts of influenza A viruses. These viruses rarely caused disease in ducks until 2002, when some H5N1 strains became highly pathogenic. Here we show that these H5N1 viruses are reverting to nonpathogenicity in ducks. Ducks experimentally infected with viruses isolated between 2003 and 2004 shed virus for an extended time (up to 17 days), during which variant viruses with low pathogenicity were selected. These results suggest that the duck has become the “Trojan hors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
326
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(355 citation statements)
references
References 24 publications
16
326
2
4
Order By: Relevance
“…Higher levels of viral shedding were detected in oropharyngeal swabs than in cloacal swabs in both age groups, which is consistent with the reported shift from the traditional enteric system of spread of AI viruses to respiratory spread 9 , 25 , 30 , 31 . Similar levels of viral shedding were also detected in oropharyngeal and cloacal swabs from both age groups, which may have implications for the transmission and geographical spread of these H5N1 clade 2.2 viruses.…”
Section: Discussionsupporting
confidence: 84%
“…Higher levels of viral shedding were detected in oropharyngeal swabs than in cloacal swabs in both age groups, which is consistent with the reported shift from the traditional enteric system of spread of AI viruses to respiratory spread 9 , 25 , 30 , 31 . Similar levels of viral shedding were also detected in oropharyngeal and cloacal swabs from both age groups, which may have implications for the transmission and geographical spread of these H5N1 clade 2.2 viruses.…”
Section: Discussionsupporting
confidence: 84%
“…These results also suggested that post-harvest rice paddy fields, which are equally attractive to wild birds and poultry, may have actedas a meeting point between the two. With laboratory studies indicating that domestic ducks may develop HPAI H5N1 virus sub-clinical infections (Hulse-Post et al, 2005), the frequent movements of duck flocks, brought together in night shelters which are often located within villages, and from where live birds and eggs enter the market chain, made healthy ducks important potential virus transmitters and amplifiers of infection (Songserm et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, HP A/duck/Vietnam/40D/04 (H5N1) was used (Hulse-Post et al, 2005;Phuong et al, 2010). Virus stock was grown in 10-day-old embryonated chicken eggs at 37 C. The allantoic fluid was harvested, and aliquots were stored at 280 C until use.…”
Section: Viral Strainmentioning
confidence: 99%